A desmotivação dos alunos de escola pública da 8ª série/9º ano pelo ensino-aprendizagem de língua inglesa - Aguiar, Vera Aparecida (2013)
This paper aims to investigate the possible factors to the students desmotivation in grade 8th/9th years in teaching and learning of English language in public school and how to awaken their interest for the proposed activities in the classroom. The theoretical reference that supports the present study is based on the concepts of motivation and its importance in second language acquisition in view of Dörnyei (1998), Brown (2000), Ushioda and Dörnyei (2012) and the question of motivation in school context and importance in studying a foreign language through the perspective of Bznueck (2001), Pozo (2002), Moita Lopes (2001), Leffa (2002), Celani (2004), among others, and in the Brazilian National Curriculum Parameters (Parâmetros Curriculares Nacionais – LE - Brasil, 1998). The results show that the students are not really unmotivated in studying English language, but with the methodology in which language is taught, because it does not meet their needs and perspectives. Keywords: unmotivated, motivation, interest, students, English language, teacher, activity